The Marine Fisheries in Bulgaria's Exclusive Economic Zone, 1950–2013 - Keskin, Çetin; Ulman, Aylin; Zylich, Kyrstn; Raykov, Violin; Daskalov, Georgi M.; Pauly, Daniel; Zeller, Dirk (Frontiers in Marine Science, 2017)
The aim of this study is to reconstruct the total historic catch of Bulgarian marine fisheries in their Exclusive Economic Zone for the time period 1950-2013, including unreported landings, discards, recreational and subsistence catches from the ecosystem. The landings data officially reported by Bulgaria to the Food and Agriculture Organization of the United Nations for the Mediterranean and Black Seas (FAO Area 37) were revised in line with all available information. The reconstructed total catch for 1950-2013 was 1.7 times the (adjusted) baseline data reported by Bulgaria to FAO and 1.5 times the unadjusted data as reported by FAO. This study revealed major deficiencies which exist in the officially reported Bulgarian catch data, foremost being the large amount of unreported industrial catches, especially for the last two decades. Furthermore, the exclusion of some fisheries sectors, notably the absence of data on the subsistence and recreational fisheries in reported data are also noteworthy.